Cost Analysis of Initial Treatment With Endovascular Revascularization, Open Surgery, or Primary Major Amputation in Patients With Peripheral Artery Disease. (August 2018) - Tang, Linda; Paravastu, Sharath C. V.; Thomas, Shannon D.; Tan, Elaine; Farmer, Eric; Varcoe, Ramon L.
Purpose: To compare the total initial treatment costs for open surgery, endovascular revascularization, and primary major amputation within a single-payer healthcare system.Methods: A multicenter, retrospective analysis was undertaken to evaluate 1138 patients with symptomatic peripheral artery disease (PAD) who underwent 1017 endovascular procedures, 86 open surgeries, and 35 major amputations between 2013 and 2016. A cost-mix analysis was performed on individual patient data generated for selected diagnosis-related groups. Mean costs are presented with the 95% confidence interval (CI).Results: There was no intergroup difference in demographics or private health insurance status. However, the amputation group had a higher proportion of emergency procedures (68.6% vs 13.3% vs 27.9%, p<0.001) and critical limb ischemia (88.6% vs 35.9% vs 37.2%, p<0.001) compared with the endovascular therapy and open surgery groups, respectively. The endovascular revascularization group spent less time in hospital and used fewer intensive care unit (ICU) resources compared with the open surgery and major amputation groups (hospital length of stay: 3.4 vs 10.0 vs 20.2 days, p<0.01; ICU: 2.4 vs 22.6 vs 54.6 hours, p<0.01), respectively. While mean prosthetic and device costs were higher in the endovascular group [AUD2770 vs AUD1658 (open) and AUD1219 (amputation), p<0.01], substantial disparities were observed in costs associated with longer operating theater times, length of stay, and ICU utilization, which resulted in significantly higher costs in the open and amputation groups. After adjusting for confounders, the AUD18, 396 (95% CI AUD16, 436 to AUD20, 356) mean cost per admission for the endovascular revascularization group was significantly less (p<0.001) than the open surgery (AUD31, 908, 95% CI AUD28, 285 to AUD35, 530) and major amputation groups (AUD43, 033, 95% CI AUD37, 706 to AUD48, 361).Conclusion: Endovascular revascularization procedures for PAD cost the health payer less compared with open surgery and primary amputation. While devices used to deliver contemporary endovascular therapy are more expensive, the reduction in bed days, ICU utilization, and related hospital resources results in a significantly lower mean total cost per admission for the initial treatment.